Tungku Krusibel dengan Economizer untuk Praktik Pengecoran di Jurusan Pendidikan Teknik Mesin FT UNY - Arianto Leman; Tiwan Tiwan; Mujiyono Mujiyono (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
This research was aimed at developing economizer on aluminum crucible furnace to improve the furnace's performance. The research implements a Research and Development method. The economizer effects was determined from the performance test. The furnace were being tested with and without economizer at the same process condition. The developed furnace exhaust have the same diameter with the gas burner inlet. The exhaust was extended and curved to serve as an economizer. Aluminum of 11.78 kg can be melted with the economizer effects in 60 minutes, and only required 2.6 kg of LPG, whereas without economizer it required 3.1 kg LPG in 80 minutes for the same amounts of Aluminum. Penelitian ini bertujuan menambahkan economizer pada tungku pelebur aluminium untuk memperbaiki performa tungku. Metode Research and Development diterapkan untuk pengembangan tungku. Efek penggunaan economizer ditentukan dari uji kinerja. Tungku diuji coba tanpa dan dengan economizer pada kondisi proses yang sama. Saluran buang pada tungku berdiameter sama dengan saluran masuk. Saluran dibuat memanjang dan berbelok berfungsi sebagai economizer. Aluminium 11,78 kg dapat dicairkan memakai economizer dalam 60 menit dan membutuhkan 2,6 kg gas LPG, sedang tanpa economizer membutuhkan 3,1 kg gas LPG dan waktu 80 menit.